2008
DOI: 10.1016/s1472-6483(10)60465-8
|View full text |Cite
|
Sign up to set email alerts
|

Adding phytoestrogens to clomiphene induction in unexplained infertility patients – a randomized trial

Abstract: This study investigated the role of oral phytoestrogens in improving pregnancy rate and cycle outcomes with clomiphene citrate. Patients with unexplained infertility and recurrent clomiphene citrate induction failure, were randomly divided into two groups: group I (n = 60) and group II (n = 59). Both groups received clomiphene citrate 150 mg per day (days 3 to 7). Group I received additional oral phytoestrogen (Cimicifuga racemosa) 120 mg/day from days 1 to 12. Human chorionic gonadotrophin (HCG) injection (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 47 publications
5
46
0
2
Order By: Relevance
“…Three RCTs and 2 uncontrolled trials examined efficacy for hot flashes as their primary endpoint, [26][27][28][29][30] whereas 5 uncontrolled trials and 12 RCTs assessed the effect of black cohosh on estrogen responsive tissues. 9,10,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] These studies are summarized in Tables 3, 4, and 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three RCTs and 2 uncontrolled trials examined efficacy for hot flashes as their primary endpoint, [26][27][28][29][30] whereas 5 uncontrolled trials and 12 RCTs assessed the effect of black cohosh on estrogen responsive tissues. 9,10,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] These studies are summarized in Tables 3, 4, and 5.…”
Section: Resultsmentioning
confidence: 99%
“…35 All other studies reported no impact on FSH or LH level, with the exception of Duker 43 , who reported a significant decrease in LH only (P < .05). 10,30,32,35,37,38,[41][42][43][44] Of 3 uncontrolled trials assessing mammographic density, all 3 studies reported no significant changes overall with black cohosh use. 31,34,35 In a large trial of 400 participants, the authors reported an increase observed in one participant only, with higher density, after using black cohosh for the 1-year treatment period.…”
Section: Effect On Estrogen Responsive Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometrial thickness, serum progesterone, and clinical pregnancy rate were significantly higher in group I (8.9 ± 1.4 mm versus 7.5 ± 1.3 mm, P \ 0.001; 13.3 ± 3.1 ng/ml versus 9.3 ± 2.0 ng/ml, P \ 0.01; 36.7 % versus 13.6 %, P \ 0.01, respectively). The study concluded that adding C. racemosa rhizome dry extract to clomiphene citrate induction can improve the pregnancy rate and cycle outcomes in these couples [25].…”
Section: Discussionmentioning
confidence: 96%
“…Shahin et al's study [25] investigated the role of oral phytoestrogens in improving pregnancy rate and cycle outcomes with clomiphene citrate. Patients with unexplained infertility and recurrent clomiphene citrate induction failure were randomly divided into two groups: group I (n = 60) and group II (n = 59).…”
Section: Discussionmentioning
confidence: 99%